Pengaruh KB Suntik Tiga Bulan Depo Medroksi Progesteron Acetate (DMPA) terhadap Kenaikan Berat Badan di Puskesmas Tanah Abang Jakarta Tahun 2019 - Dina Raidanti (Neolectura, 2021)
The most popular method of contraception is injectable contraception. One of the most widely used types of injection kb methods are injectable contraceptives with the type of Noretisterone Enentat (NETEN), Depo Medroxy Progesterone Acetate (DMPA) and Cyclofem. Although widely used, injectable contraceptives have drawbacks. One of the side effects that arise is irregular menstrual patterns such as amenorrhea, menorrhea and spotting, low eversibility, and weight gain of acceptors. Destination:. There is an increase in body weight in mothers, therefore this study aims to determine the relationship between the use of kb injections and maternal weight gain at the Tanah Abang Public Health Center, Jakarta. Methods: This study is an observational analytic study with a case control design to analyze the extent to which risk factors affect The occurrence of an effect in this case is an increase in body weight of the DMPA-type injection family planning acceptors. Result :. Based on the increase in body weight in the case group, 54.2% of DMPA injection family planning acceptors did not show any relative weight gain. However, 59.2% of the DMPA injection family planning acceptor cases experienced weight gain. The increase that occurs between 1 - 2 Kg, further DMPA injection family planning acceptors are at risk of experiencing weight gain 2,310 times faster when compared to non DMPA family planning acceptors. However, KB with the DMPA injection method is not the main factor that causes weight gain, this is indicated by the results of the significance test with Cochran & Mantel Haenszel, the results obtained are X2 count (2.089) <X2 Table (3.841) or p (0.148)> ? (0.050) and CI (0.872; 6.118).